Morphological Response of Bawang Dayak (Eleutherine americana Merr.) on Plant Growth Promoting Rhizobacteria Application - Ariska, Fera; Marlin, Marlin; Widodo, Widodo (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2020)
Bawang dayak is the important medicinal plant that need to be developed in cultivation techniques and production. The use of Plant Growth Promoting Rhizobacteria (PGPR) recently known to be effective to increase plant growth and yield. The research aimed to determine the optimal concentration and immersion time of PGPR on the growth and yield of bawang dayak. The experiment was arrange in complete randomized block design (RCBD) consisting of two factors. The first factor is the concentration of PGPR with 4 levels namely K0 = 0 g L-1, K1 = 5 g L-1, K2 = 10 g L-1 and K3 = 15 g L-1. The second factor is immersion time of seed, namely P1 = 10 minutes, P2 = 20 minutes, P3 = 30 minutes and P4 = 40 minutes. The results showed that there was an interaction between concentration and immersion time of PGPR giving effect to the number of leaves and the number of tillers. The immersion time of PGPR for 10 minutes with a concentration of 15 g L-1produced the highest number of leaves (58 leaves) and produced the highest number of tillers (27.67 tillers). The treatment of PGPR concentration or immersion time of PGPR singly did not affect all observed variables of growth and yield of bawang dayak.